Autogestión and water sharing networks in Puerto Rico after Hurricane María. Issue 6 (18th August 2021) - Roque, Anais; Wutich, Amber; Brewis, Alexandra; Beresford, Melissa; García-Quijano, Carlos; Lloréns, Hilda; Jepson, Wendy
ABSTRACT: Puerto Rico's residents were left without water services for up to nine months in the wake of hurricanes Irma and María (2017). Further, it was clear that there were no viable plans for addressing water provision gaps in anticipation of future hazards. In response, Puerto Ricans initiated autogestión, a strategy to secure survival through self-provisioning. Utilizing mixed methods, we reveal two different emergent forms of autogestión water self-provision in three differently serviced Puerto Rican communities. These provide an informed reflection on the trade-offs and pitfalls of reliance on autogestión for water security in the wake of disaster.